Good-bye, Mr. Chips - Hilton, James, 1900-1954.; Kossin, Sanford (New York : Bantam Books, 1986)
A retired teacher reminisces about his years at Brookfield School, the thousands of boys he had known, and his happy marriage.
7.0
Young Adult
Keywords: Schools -- Fiction; Teachers -- England -- Fiction; School stories; Teachers -- England -- Fiction; England -- Fiction; England -- Fiction